2018
DOI: 10.1007/s11837-018-2777-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Electric-Magnetic Hydrodynamics in Solidification: In Situ Observations and Theory

Abstract: Solidification of liquid metals contains all the ingredients for the development of the thermo-electric (TE) effect, namely liquid-solid interface and temperature gradients. The combination of TE currents with a superimposed magnetic field gives rise to thermo-electromagnetic (TEM) volume forces acting on both liquid and solid. This results in the generation of fluid flows, which considerably modifies the morphology of the solidification front as well as that of the mushy zone. TEM forces also act on the solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In the presence of an applied magnetic field, the TE currents interact generating a Lorentz force that drives flow, convectively transporting both heat and mass. Significant changes to solidification processes due to TEMHD have been observed experimentally and predicted theoretically in situations ranging from the low thermal gradient and slow solidification typical of directional solidification processes [28][29][30] to the high thermal and rapid solidification process of high undercooled growth [31,32]. In terms of solidification conditions, AM thermal gradients are high with moderate solidification velocities compared to high undercooled growth, and, therefore, TEMHD effects could be quite significant.…”
Section: Introductionmentioning
confidence: 98%
“…In the presence of an applied magnetic field, the TE currents interact generating a Lorentz force that drives flow, convectively transporting both heat and mass. Significant changes to solidification processes due to TEMHD have been observed experimentally and predicted theoretically in situations ranging from the low thermal gradient and slow solidification typical of directional solidification processes [28][29][30] to the high thermal and rapid solidification process of high undercooled growth [31,32]. In terms of solidification conditions, AM thermal gradients are high with moderate solidification velocities compared to high undercooled growth, and, therefore, TEMHD effects could be quite significant.…”
Section: Introductionmentioning
confidence: 98%
“…33) In addition, we have found that TEMF also cause a movement of equiaxed grains in suspension by using x-ray in situ and real-time observations under static magnetic field. 34,35) To gain more insight, the solidification microstructures and the maximum value of computed TEMC and the von Mises stress at various growth rates and magnetic field intensities under the temperature gradient of 104 K/cm are plotted in Fig. 8.…”
Section: The Cet Mechanism With Asmfmentioning
confidence: 99%
“…) and it is well known that applying a static magnetic field changes the melt flow leading to electromagnetic damping [8] or alternatively, a travelling field (including a rotating magnetic field) leads to electromagnetic stirring (EMS) [9,10]. A static magnetic field has also been seen to drive flow through its interaction with inherent thermoelectric currents [11][12][13][14], generated in solidifying alloys due to spatial variations in temperature and Seebeck coefficient [11,[15][16][17]. This thermoelectric Lorentz force ( #! )…”
Section: Introductionmentioning
confidence: 99%
“…This thermoelectric Lorentz force ( #! ) produces flow in the mushy zone between growing dendrites, an MHD phenomenon known as Thermoelectric Magnetohydrodynamics (TEMHD) [11,13,15,18]. !"…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation